Identification of familial networks reveals sex-specific density dependence in the dispersal and reproductive success of an endangered ungulate - McFarlane, Samantha; Manseau, Micheline; Jones, Teri B.; Pouliot, Darren; Mastromonaco, Gabriela; Pittoello, Gigi; Wilson, Paul J. (Frontiers in Ecology and Evolution, 2022)
Density is an important demographic parameter that is commonly overlooked in studies of wild populations. Here, we examined the effects of variable spatially explicit density on a range of demographic parameters in a wild population of a cryptic ungulate, boreal woodland caribou (Rangifer tarandus caribou). Using noninvasive genetic sampling, we applied spatial capture-recapture methods with landscape covariates to estimate density of boreal woodland caribou across a 108,806 km2 study area. We then created a familial network from reconstructed parent-offspring relationships to determine whether spatial density influenced sex-specific individual reproductive success, female pregnancy status and dispersal distance. We found that animal density varied greatly in response to land cover types and disturbance; animal density was most influenced by landscape composition and distance to roads varying from 0 in areas with >20% deciduous cover to 270 caribou per 1,000 km2 in areas presenting contiguous older coniferous cover. We found that both male and female reproductive success varied with density, with males showing higher probability of having an offspring in higher density areas, and the opposite for females. No differences were found in female pregnancy rates occurring in high- and low-density areas. Dispersal distances varied with density, with offspring moving shorter distances when parents were found in higher density areas. Familial networks showed lower closeness centrality and lower degree centrality for females in higher density areas, indicating that females found in higher density areas tend to be less broadly associated to animals across the range. Although high density areas do reflect good quality caribou habitat, the observed decreased closeness and degree centrality measures, dispersal rates and lower female recruitment rates suggest that remnant habitat patches across the landscape may trigger positive feedbacks.